Planning: The key to institution building in Nigeria an appraisal of the activities of universal basic education commision - Abdullahi, Danjuma; Abdullah, Siti Alida John; Abdulsomad, Kammaruddin (2014)
Planning is one of the fundamental functions of management at the same time institution success depend on the proper planning and implementation of government policy and program-me, since the launching of universal basic education in Nigeria there are a lot of outcries that the data for planning is not being utilized, as a result it create problems such as inadequate finance, poor management of the institution and lack of commitment of government for the achievement of aims and objectives of the UBE in Nigeria.The data were sourced through interviews conducted with the stakeholders of basic education.Ten respondents were interviewed,the study also used secondary data such as newspapers, journals and annual reports of the organization in focus.Atlas ti 7 was used to analyse the data.The findings reveals poor data generation, poor coordination, lack of utilization of the data for planning and the paper recommends improve in data collection, commitment of government, effective coordination and making used of the data.